GREEN HALAL: SINERGI INDUSTRI HALAL DAN PEMBANGUNAN BERKELANJUTAN - Anisah, Dewi (University of Islam Malang, 2024)
The Halal industry and sustainable development are two progressive issues closely related in the future. Industrial practices, particularly in the food industry, generate a significant amount of waste, and consumer awareness of environmental issues has sparked interest in